Pattern Analysis of Regional Energy Consumption Based on Integrated Energy Measurement Data - Xingang WANG; Fang ZHAO; Wenjun ZHU (Zhongguo dianli, 2022)
The spatio-temporal pattern of users’ energy consumption can offer an important guideline for power system planning, and it is also one of the most important basis for power grid construction. Through widely deployed new-type advanced metering infrastructures, power grid operators are able to analyze the users’ energy consumption patterns, which can promote the efficient operation of power grids. Towards regional user profile for energy consumption, a regional energy consumption pattern analysis approach is proposed based on integrated energy measurement data. Using multi-meter integration energy-consumption acquisition system, the gas consumption data is introduced for analysis. The hierarchical clustering and self-organized maps (SOM) methods are used to describe the energy consumption patterns. Simulation and experimental results show that the proposed method is of practical use in energy consumption analysis and conducive to discovering high energy-consumption regions, which is helpful for power grid operators to formulate power system planning schemes.